-p*p=

Simple and best practice solution for -p*p= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -p*p= equation:


Simplifying
-1p * p = 0

Multiply p * p
-1p2 = 0

Solving
-1p2 = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Divide each side by '-1'.
p2 = 0

Simplifying
p2 = 0

Take the square root of each side:
p = {0}

See similar equations:

| y^2-2y+1=16 | | 0.125(x+230)=200 | | -2(3x-5)= | | 2y+16=180 | | 2(2y+16)=7y-7 | | 188-5x=40x+18 | | (3z+5)+(2z-10)+90=180 | | 3n-5=-(6+5n) | | (4y+8)+(3y-9)+90=180 | | 2(x+1)-x(x+1)=0 | | b-1819=2300 | | 3(d+6)=12(d+3) | | -1.3+0.4= | | 12x+20=3x+209 | | 4x+10=2(3x-11) | | 7x+21=7 | | 6z+6=2(4z-16) | | 2x^2+9x-1= | | 12-9x=74-23x | | -5x+2=2 | | 24x+(-2)=2x+3 | | (2x+1)3-(x+4)5=5-(5x+1) | | g=3+h | | 75x-5x=8x+32 | | 667=29j | | 6+4=10 | | 4z+9=45 | | f=2g | | f=29 | | 30t+42m=18600 | | 28g=-364 | | 4z+9=180 |

Equations solver categories